Multi-constraints adaptive finite-time integrated guidance and control design - Zhang, Denghui; Ma, Ping; Wang, Songyan; Chao, Tao (Aerospace science and technology, 2020)
The skid-to-turn hypersonic vehicle is subject to the complex aerodynamic uncertainty and random wind disturbance. Besides, actuator saturation and full state constraints, consisting of attack angle, sideslip angle, bank angle and body angular rates should be considered to guarantee structural safety and flight stability. However, these uncertainties and constraints will lead to a great challenge in the integrated guidance and control (IGC) design. To address this issue, a novel multi-constraints adaptive finite-time IGC scheme, based on barrier Lyapunov function (BLF), finite-time stability theory and back-stepping method, is proposed in this paper. While the piecewise saturation is employed to restrict the virtual commands of the constrained states, BLF is used to guarantee the compensated tracking errors bounded. Moreover, three novel auxiliary systems are constructed to eliminate the negative effect, suffered from possible saturation. Meanwhile, adaptive technique is adopted to estimate the unknown upper bound of disturbances. With the aid of Lyapunov stability analysis, the states can be proved to remain in the constrained set and converge into the small regions in a finite time. Numerical simulations are performed to demonstrate the effectiveness and robustness to the initial state deviations and aerodynamic parameter uncertainty of the proposed adaptive IGC scheme.